PENERAPAN MEDIA BENDA KONKRET UNTUK MENINGKATKAN PEMAHAMAN KONSEP PENJUMLAHAN DAN PENGURANGAN PESERTA DIDIK KELAS II SD NEGERI 1 CIPETIR KABUPATEN SUKABUMI - Dede Lismayani; Astri Sutisnawati; Lutfi Hamdani Maula (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research was motivated by the low understanding of addition and subtraction concepts among second-grade students at SD Negeri 1 Cipetir, Sukabumi Regency. Based on initial observations, students experienced difficulties in understanding arithmetic operation concepts because learning was still abstract and did not adequately utilize learning media that matched students’ developmental characteristics. This study aimed to improve students’ understanding of addition and subtraction concepts through the use of concrete object media for second-grade students at SD Negeri 1 Cipetir, Sukabumi Regency.The study employed a Classroom Action Research (CAR) method conducted in two cycles. Each cycle consisted of planning, action implementation, observation, and reflection stages. The subjects of the study were 22 students, consisting of 13 male students and 9 female students. Data collection techniques included observation, tests, interviews, and documentation. The data were analyzed using descriptive quantitative and descriptive qualitative techniques.The results of the study showed that the use of concrete object media could improve students’ understanding of addition and subtraction concepts. This was indicated by an increase in the average score from 32 in the pretest to 55 in Cycle I Meeting 1, increasing to 61 in Cycle I Meeting 2, then to 65 in Cycle II Meeting 1, and reaching 85 in Cycle II Meeting 2. The percentage of learning mastery also increased from 0% at the initial condition to 86% at the end of the study. In addition, students’ learning activities improved during the learning process. Therefore, concrete object media is effective in improving elementary school students’ understanding of addition and subtraction concepts.